Comparison between a laser lancing device and lancet for capillary blood sampling, capillary blood hemoglobin measurement, and blood typing. Issue 10 (15th July 2021) - Kim, Jeeyong; Yoon, Soo‐Young; Lim, Chae Seung; Yoon, Jung
Abstract: Background: Blood donor screening includes tests using capillary blood, which is usually obtained by finger pricking using a lancet; however, the lancet has some shortcomings, such as skin puncture pain and needle stick injury. Recently, laser lancing devices for finger‐prick sampling have been developed. We compared capillary blood Hb (cHb) levels and blood typing results obtained using a laser lancing device with those obtained using a lancet. Study design and methods: cHb levels, blood typing results, and skin puncture pain scores were assessed in 191 participants. Finger‐prick sampling was performed using LMT‐1000 (LaMeditech, Seoul, Korea) and a lancet on the same finger on different hands. Paired venous Hb (vHb) levels were assessed in 103 participants using an automated hematology analyzer and compared with the cHb levels obtained using both lancing devices. Results: The paired cHb results obtained with the laser lancing device and lancet showed a strong correlation ( r  = 0.927, p  < .001) without any significant difference ( p  = .113) and a substantial agreement ( κ  = 0.654) for the identification of participants with a low Hb level (<12.5 g/dl). cHb levels were significantly higher than vHb levels with both lancing devices (mean differences: 0.27–0.43 g/dl). The results of blood typing using the laser lancing device showed 100% accuracy. Use of the laser lancing device showed significantly lower skin puncture pain scores ( p  < .001). Conclusion: Use of a laser lancing device for capillary Hb measurement and blood typing showed accurate results, with significantly reduced skin puncture pain. Laser lancing devices could be feasible for donor screening tests.